Cerebrospinal fluid HIV RNA in persons living with HIV. Issue 5 (25th January 2018) - Di Carlofelice, M; Everitt, A; Muir, D; Winston, A
Abstract : Objectives: Despite adequate suppression of plasma HIV RNA, viral escape in cerebrospinal fluid (CSF) is widely reported. Rates of CSF HIV RNA escape vary in the literature. In persons living with HIV (PLWH) undergoing lumbar puncture examination for clinical reasons, we assessed rates of CSF HIV RNA escape. Methods: Persons living with HIV attending a designated HIV neurology service undergoing CSF assessment for clinical reasons between January 2015 and April 2017 were included in the study. CSF HIV RNA escape was defined as HIV RNA ≥ 0.5 log10 HIV‐1 RNA copies/mL higher than plasma HIV RNA or detectable CSF HIV RNA when plasma HIV RNA was < 20 copies/mL. Clinical factors associated with CSF HIV RNA were assessed using logistic regression modelling. Results: Of 38 individuals, 35 were receiving antiretroviral therapy, 30 were male and their mean age was 51 years. Clinical reasons for CSF assessment included investigation for cognitive decline ( n  =   25), early syphilis ( n  =   4) and other central nervous system (CNS) conditions ( n  =   9). HIV RNA was detectable in plasma and CSF in seven and six individuals, respectively, with two individuals (5.3%) meeting the definition of CSF escape. Detectable CSF HIV RNA was associated with a detectable plasma HIV RNA ( P  <   0.001) and a history of known antiretroviral drug resistance mutations ( P  =   0.021). Conclusions: The prevalence of CSF viral escape in PLWH undergoing lumbar puncture examination for clinical reasons is lower than previously reported.